Penataan Reklame Pada Koridor Jalan Andi Pangeran Pettarani Kota Makassar - Nirmala Marzuki; Bambang Heryanto; Isfa Sastrawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2013)
Advertising signs as one of the street furniture has its own characteristic and potential about the visual quality in an urban areas. Along with the growth of the information media in urban areas, the quantity of advertising signs especially commercial advertising may cause an impact to the arrangement of advertisement condition. Andi Pangeran Pettarani street as one of the main street in Makassar City being an objective place for advertisements, either commercial and social advertising. Along this street, we can find some advertisement with many kinds of type and shapes. The aim of this research is to arrange the advertising signs at corridor based on the placement of advertising which can be found along the street. Based on the research, we can find the characteristic and an impact of the advertisement arrangement which caused by any deviation. By this analysis result, we can formed criteria of advertising arrangement and realize it to the corridor based on its land use.